Snack-media platform market segmentation based on user heterogeneity: A Q-methodology approach - Suwon Kim (International Telecommunications Society (ITS), 2018)
The entire media market competing for user attention is currently leaning toward snack-media, and it has become an undoubtedly important media industry sector. As its economic impacts grow, the snack-media market structure has become increasingly critical as a national concern. The near-monopolistic market, dominated by the global giant platforms, e.g. YouTube, should not be desirable for all the stakeholders in the local ICT and media industry. Given that network effects potentially reinforce the market dominance of the global giants, differentiation should be the most viable option for the local snack-media platforms. This study aims to segment the snack-media market based on user heterogeneity and to discuss corresponding strategies of the local platforms, adopting Q-methodology. The results revealed five user types, and they were located in a positioning map with two axes of the level of efficiency-pursuit and centered gratification. The local snack-media platforms' counter-strategies were suggested corresponding to the taxonomy.
Keywords: 330